La Galice au XXe siècle : économie, culture et autogouvernement - Ramón Villares (Cahiers de Civilisation Espagnole Contemporaine)
The article deals with the evolution of Galicia in the 20th century until the years of autonomy, analyzing the economic and social changes in a connected way, with the evolution of political consciousness and the creation of a national identity. The modernization of Galicia had its main pillars in the maritime industries and in the specialization of its agriculture by small owners. The massive emigration to America, then to Europe and to the most industrialized regions of Spain, was another essential pillar. And to all this was added the mutation of cultural regionalism into political nationalism, reaching its maturity during the Second Republic. On those bases and after a « long night of stone » during the Franco dictatorship, autonomous Galicia was built, as one of the three « historical nationalities », with Catalonia and the Basque Country, within the State of Autonomies designed by the Constitution of 1978.